On the approximate solution of nonlinear Volterra-Fredholm integral equations on a complex domain by Dzyadyk’s method - Rizk, M. M.; Zaher, S. L. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
In 1980–1984, V. K. Dzyadyk suggested and modified an iterative approximation method (IA-method) for numerical solution of the Cauchy problem y′=f(x,y), y(x 0)=x0. Particular cases of nonlinear mixed Volterra-Fredholm integral equations of the second kind arise in the mathematical simulation of the space-time development of an epidemic. This paper is concerned with the approximate solution of integral equations of this type by the Dzyadyk method on complex domains. Finally, we test this method numerically by four different examples.